Community Partnership Program (PKM) Procurement and Management Efforts of Vocational School Libraries August 17, 1945 According to the National Library Standards Agency (BSNP) of the Republic of Indonesia - Ardianik Ardianik; Wahyu Widayati (Kontribusia : Research Dissemination for Community Development, 2022)
Partners in the implementation of this community partnership program are SMK 17 Agustus 1945 which is located on Jalan Nginden Semolo no.44 Surabaya. The facilities owned are IT-based, it's just that the obstacles faced by schools in supporting the teaching and learning process, especially the facilities and convenience of libraries, have not met the national library standards. Based on the input of teachers and library staff as well as direct observations made by the service team, there are several problems, namely: 1) There is no arrangement of library material collections according to their field of knowledge; 2) There is no book cataloging in accordance with the field; 3) Inventory of library materials has not been managed properly and correctly, by providing a book slip for each book; 4) There is no circulation service yet, because officers are burdened with routine public relations activities and lack of library personnel; 5) There is no guidebook in managing library materials, officers have not used standard guidelines. There are two stages in implementing the solution that must be completed with partners, namely: 1) the planning stage which includes: coordination with library staff, teachers, and school principals as initial input, direct observation to obtain evidence related to initial input; 2) Implementation phase which includes: Arrangement and classification of library collections, cataloging library collections, inventory, making library circulation services, making manuals. The results of the community service activities concluded that there were significant differences before and after the procurement and management of the library. This is evident from the results of activities in the form of classification, the arrangement of library collections has been well realized, the room layout is neatly arranged, cataloging library collections, numbering and installation of slips have been installed properly, making library circulation services, and making library management manuals. manual has been realized. From a series of community service activities, it has a success rate of 100%. This is shown from all activities that have been completely completed and the results can be enjoyed by students, teachers and visitors to the SMK 17 August 1945 Library and no less important for the sake of school accreditation.